Rhodotorula kratochvilovae CCY 20-2-26-The Source of Multifunctional Metabolites - Byrtusová, Dana; Szotkowski, Martin; Kurowska, Klára; Shapaval, Volha; Márová, Ivana (Microorganisms, 2021)
Multifunctional biomass is able to provide more than one valuable product, and thus, it is attractive in the field of microbial biotechnology due to its economic feasibility. Carotenogenic yeasts are effective microbial factories for the biosynthesis of a broad spectrum of biomolecules that can be used in the food and feed industry and the pharmaceutical industry, as well as a source of biofuels. In the study, we examined the effect of different nitrogen sources, carbon sources and CN ratios on the co-production of intracellular lipids, carotenoids, β-glucans and extracellular glycolipids. Yeast strain R. kratochvilovae CCY 20-2-26 was identified as the best co-producer of lipids (66.7 ± 1.5% of DCW), exoglycolipids (2.42 ± 0.08 g/L), β-glucan (11.33 ± 1.34% of DCW) and carotenoids (1.35 ± 0.11 mg/g), with a biomass content of 15.2 ± 0.8 g/L, by using the synthetic medium with potassium nitrate and mannose as a carbon source. It was shown that an increased C/N ratio positively affected the biomass yield and production of lipids and β-glucans.